2013
DOI: 10.1007/s11605-013-2235-0
|View full text |Cite
|
Sign up to set email alerts
|

What Patients and Surgeons Should Know About the Consequences of Appendectomy for Acute Appendicitis After Long-Term Follow-Up: Factors Influencing the Incidence of Chronic Abdominal Complaints

Abstract: In conclusion, the results of our study show that after follow-up of 7 years, the incidence of abdominal complaints was not influenced by operative technique or whether acute appendicitis was complicated or not. This finding does not support a causative role for adhesions with regard to chronic abdominal complaints. Our data enables surgeons to inform their patients about the long-term results of appendectomy, whether it was complicated or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This is equivalent to other retrospective quality-of-life studies reporting follow-up percentages between 37 and 52% after 2.5 to 7 years of follow-up [2, 42-44]. Baseline characteristics did not significantly differ between R and NR suggesting that the R group reflects the whole study population.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This is equivalent to other retrospective quality-of-life studies reporting follow-up percentages between 37 and 52% after 2.5 to 7 years of follow-up [2, 42-44]. Baseline characteristics did not significantly differ between R and NR suggesting that the R group reflects the whole study population.…”
Section: Discussionsupporting
confidence: 74%
“…It has been suggested that traction of adhesions on the peritoneum and viscera, nerve fibers in adhesions itself, or changes in the nervous system might contribute to chronic abdominal pain caused by adhesions when other organic and functional diseases are excluded [1, 4]. However, other studies and this data do not support that relationship [2, 3]. …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The literature on outpatient/day case appendicectomy focuses on feasibility and safety of the procedure, with most large volume studies focussing on outcomes such as complication rate of surgery [[6], [7], [8], [9], [10]], with follow-up periods of less than 6 months [1,11]. …”
Section: Introductionmentioning
confidence: 99%
“…6,37,38 A 2013 study did a 7-year follow-up of patients after appendectomy and found no difference in long term belly complaints between patients undergoing open or laparoscopic appendectomy. 39 …”
mentioning
confidence: 99%